The impact of school-based healthy eating education on adolescent girls’ diet and body image: A reflexive thematic analysis - Hannah Brighty; Jasmin Langdon-Daly (Journal of Health Psychology, 2026)
Healthy eating education has been compulsory in English schools since 2020, yet concerns persist about its effectiveness in reducing childhood obesity and its potential contribution to rising eating disorder rates among adolescent girls. This study therefore explored girls’ experiences and perceptions of healthy eating education and its impact on diet and body image. Forty girls aged 16–18 completed a qualitative survey, and data were analysed using reflexive thematic analysis. Four themes were constructed: ‘Good Food, Bad Food’, reflecting perceptions of rigid food messaging; ‘Moral Narratives in Health and Diet’, highlighting perceptions that eating was framed as a matter of morality; ‘The Healthy Eating Disconnect’, capturing tensions between school guidance and structural barriers; and ‘Modernising the Curriculum’, reflecting calls for education on body image and eating disorders. Findings suggest healthy eating education may contribute to eating disorder risk, with benefits limited by structural barriers and insufficient attention to pupils’ needs.